Smart mirror student timetable management system based on IOT platform using : Raspberry PI / Nur Afiqah Zubir - Zubir, Nur Afiqah (2019)
In the modern work, the tasks become more complex and difficult to manage which causes a lot of students complete their assignments during last minutes. This limitation of tools and devices around them which can only perform one task at a time makes the students’ life more miserable. To solve this problem, this project has developed a Smart Mirror Student Timetable Management System based on IoT Platform using Raspberry Pi. The Smart Mirror technology is one of the Smart Home device that can help the students to manage their time wisely. The aim of this project is to develop a Smart Mirror Student Timetable Management System based on IoT Platform using Raspberry Pi. For the time constraints, this project is focused on students with poor time management. So, this project will probably help these students in a smart and efficient way. In order to accomplish this project, the researcher has applied Waterfall method in the methodology phase. This method starts with requirement analysis phase, continued with planning phase, designing phase, development phase and finally testing phase. After the prototype has successfully developed, the testing is done by using functionality testing. The testing is carried on the website and the prototype itself to test whether they are functioning well or not. The result of the testing has been analysed and recorded respectively into a table formed.